Association between NoSAS score and cardiovascular disease in patients with obstructive sleep apnea - Chen, Riken; Quan, Jie; Tang, Qiujing; Chen, Zhaojun; Hu, Zhongxing; Yang, Yitian; Li, Wenxi; Su, Yihuan; Liao, Huizhao; Sun, Tingting; Chen, Qinghua; Cai, Yuli; et al. (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveObstructive sleep apnea (OSA) is a common sleep-related respiratory disorder, yet many cases remain undiagnosed. Given the significant association between OSA and various adverse health outcomes, including cardiovascular complications, early identification and intervention are essential. The NoSAS score effectively screens individuals at high risk of OSA, thereby aiding in early detection.Material and methodsData were collected from the Sleep Medicine Center at the First Affiliated Hospital of Guangzhou Medical University and the Sleep Research Institute at the Second Affiliated Hospital of Guangdong Medical University. Participants with a NoSAS score ≥8 were classified as high-risk, while those with scores <3 were classified as low-risk. Logistic regression was used to analyze the association between high-risk classification and cardiovascular disease morbidity.ResultA total of 2,164 participants with complete NoSAS score data were analyzed. In the high-risk group of 1,248 participants, cardiovascular disease incidence was 7.29%. In the adjusted model, the NoSAS high-risk group demonstrated a 2.2-fold increased risk of cardiovascular disease compared to the low-risk group (OR: 2.22, 95% CI: 1.17–4.18; p = 0.006). Age-stratified analysis indicated a significant association between NoSAS risk classification and cardiovascular disease in participants aged ≥60.ConclusionIn conclusion, the NoSAS high-risk group exhibited a higher burden of cardiovascular disease morbidity and served as an independent predictor of this condition.